Sustainable Human Resource Management Practices Impacting Employer Branding - Huseynova, Aydan (Cognitive Sustainability, 2022)
Business seeks a long-term competitive advantage to make money and stay afloat as the market grows more competitive. Human resource management is essential for gaining a competitive advantage. Companies that embrace sustainable Human Resource Management (HRM) practices have a distinct employer brand, but how an organisation’s culture plays its role indirectly in employer value proposition is scarcely studied. This paper discusses academic literature on employer branding factors by sustainable human resource management, and helps to take a holistic perspective of the present state of global acceptance of HRM.